Machining Path Optimization of Inductively Coupled Plasma Based on Surface Heat Transfer Model - Peiqi Jiao; Bin Fan; Qiang Xin; Xiang Wu; Hong Wang (Micromachines)
Inductively coupled plasma (ICP), a non-contact optical processing method, has been widely used in the preparation of fused quartz. However, the thermal effect during processing inevitably affects the stability of the removal rate, reduces the processing accuracy, and restricts the further development of plasma processing. This paper analyzes the critical temperature that affects the changes in plasma removal depth, establishes a heat transfer model for plasma jet processing through simulations, derives the heat conduction equation during processing, and obtains the critical radius corresponding to the critical temperature related to the processing speed. Additionally, this work analyzes the path temperature of the grating track used in processing and obtains the path temperature variation curve. Based on the critical radius, a staggered grating track was proposed, which verified that this track can effectively control the path temperature, thereby suppressing the error caused by the thermal effect of processing. This study not only helps to gain a deeper understanding of the heat transfer process in plasma machining, but also provides a basis for achieving high-precision plasma machining path optimization schemes.